If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 7 = -41 + -3x Reorder the terms: 7 + 5x = -41 + -3x Solving 7 + 5x = -41 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 7 + 5x + 3x = -41 + -3x + 3x Combine like terms: 5x + 3x = 8x 7 + 8x = -41 + -3x + 3x Combine like terms: -3x + 3x = 0 7 + 8x = -41 + 0 7 + 8x = -41 Add '-7' to each side of the equation. 7 + -7 + 8x = -41 + -7 Combine like terms: 7 + -7 = 0 0 + 8x = -41 + -7 8x = -41 + -7 Combine like terms: -41 + -7 = -48 8x = -48 Divide each side by '8'. x = -6 Simplifying x = -6
| .5x^2-x-4=0 | | x^5=0.09 | | C=6.29(x-1) | | -4x-9y=-25 | | 15=.85*x | | C+6=((21+c)+6)*5 | | 5/5=x | | x^2+93x+285=0 | | d^5=0.09 | | -5(-4+x)-2=x-2(x-8)-18 | | 20y=4x+24 | | 3x-5=8x+8 | | .12x+.095y=.111 | | 3t^2+5t+6= | | 12x+4=13x+6 | | 7-4(z-8)= | | 3y-13=20 | | 3(8y-4)=2(y-6) | | 1/3x3x12 | | t+1-4t=-20-1 | | -3(y+1)-(-2y-7)=4 | | 70-7(4-3x)=0 | | 3(2x+1)(x-5)=0 | | http://media.apexlearning.com/Images/200907/10/bcb418e5-498d-46f5-8693-c2b940f5e43c.gif | | 2x^2+2y^2-12x+4y=15 | | 3x+6+7x+4=180 | | (X+12)(x+7)=0 | | 0.50+0.10(3.00x+50.00)=1460 | | -(y-2)=-9y-30 | | x/40=1.43 | | 6(3x-6)=3(6x+5) | | 250x^4+128x=0 |